Terpolymer-based SIPN coating with excellent antifogging and frost-resisting properties. Issue 124 (30th November 2015) - Zhao, Jie; Meyer, Anthony; Ma, Li; Wang, Xiaojun; Ming, Weihua
Abstract : A terpolymer-based semi-interpenetrating polymer network (SIPN) coating demonstrated excellent antifogging/frost-resisting property. Abstract : We prepared an effective antifogging/frost-resisting coating by forming a semi-interpenetrating polymer network (SIPN) on the basis of a linear, random terpolymer poly(2-(dimethylamino)ethyl methacrylate- co-N -vinylpyrrolidone- co -methyl methacrylate), poly(DMAEMA- co -NVP- co -MMA), and a network of poly(ethylene glycol dimethacrylate). The excellent antifogging/frost-resisting property was mainly attributed to a balanced hydrophilicity/hydrophobicity of the terpolymer with the optimal DMAEMA/NVP/MMA molar ratio at 40/30/30. Compared to our previous work using poly(DMAEMA- co -MMA), the terpolymer-based coating demonstrated excellent antifogging property against both low- and high-temperature moist air, by eliminating the lower critical solution temperature related to the DMAEMA segments in the binary copolymer. By monitoring the coating thickness change during the fogging/frosting test, it appeared that water molecules could rapidly be absorbed into and desorbed from the terpolymer-based coating, implying long-term effectiveness of the antifogging/frost-resisting coating.